2009
DOI: 10.1152/jn.91088.2008
|View full text |Cite
|
Sign up to set email alerts
|

Functional Consequences of Neuronal Divergence Within the Retinogeniculate Pathway

Abstract: Yeh C-I, Stoelzel CR, Weng C, Alonso J-M. Functional consequences of neuronal divergence within the retinogeniculate pathway. J Neurophysiol 101: 2166 -2185, 2009. First published January 28, 2009 doi:10.1152/jn.91088.2008. The neuronal connections from the retina to the dorsal lateral geniculate nucleus (dLGN) are characterized by a high specificity. Each retinal ganglion cell diverges to connect to a small group of geniculate cells and each geniculate cell receives input from a small number of retinal gangl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 94 publications
(175 reference statements)
5
30
0
Order By: Relevance
“…In vivo recordings that correlate spiking activity of RGC-TC neuron pairs in cats and primates report one or several dominant RGCs that drive TC neuron firing (Cleland and Levick, 1971; Hubel and Wiesel, 1961; Mastronarde, 1992; Sincich et al, 2007; Yeh et al, 2009). However, additional weaker inputs were also found in cat, and notably, most RGCs drive <50% (Range 1–82%) of the postsynaptic spiking of both X and Y neurons (Rathbun et al, 2016; Usrey et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo recordings that correlate spiking activity of RGC-TC neuron pairs in cats and primates report one or several dominant RGCs that drive TC neuron firing (Cleland and Levick, 1971; Hubel and Wiesel, 1961; Mastronarde, 1992; Sincich et al, 2007; Yeh et al, 2009). However, additional weaker inputs were also found in cat, and notably, most RGCs drive <50% (Range 1–82%) of the postsynaptic spiking of both X and Y neurons (Rathbun et al, 2016; Usrey et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Others, however (especially those focusing on Y cells in cats), show that the contribution from individual RGCs exhibits greater variability, and the activity of a single retinal input rarely accounts for the entirety of the activity of its TC neuron partner (Hubel & Wiesel, 1961; Cleland & Levick, 1971; Cleland et al, 1971; Levick et al, 1972; Mastronarde, 1992). Interestingly, one study using paired recordings across both X- and Y-cells yielded examples of RGCs that drove as few as ~1% to as many as 82% of a TC neuron’s action potentials (Usrey et al, 1999); similar results later emerged in the Y pathway (Yeh et al, 2009; Rathbun et al, 2016; considered in detail in; Weyand, 2016). Furthermore, several studies corroborate anatomical observations of divergence, such that neurons with most closely matching receptive fields exhibit the greatest correlation among their firing patterns (Alonso et al, 1996; Usrey et al, 1998).…”
Section: Retinogeniculate Connectivitymentioning
confidence: 99%
“…Mastronarde (1992) concluded that ~33% of Y-cells in the A-layers were single input (based on recording from retinogeniculate pairs). Based on cross-correlations of spikes among LGN pairs, Alonso and colleagues (Yeh et al, 2009) reached a number of < 10% as being single input. Robson (1993) reconstructed retinal innervation to presumptive Y-cells (Class 1; Guillery, 1966) and observed that it was common for those cells to receive from multiple retinal axons (integration) and for the axons to innervate multiple LGN cells (multiplexing).…”
Section: Amplification/integration Of Retinal Signalsmentioning
confidence: 99%
“…Robson (1993) reconstructed retinal innervation to presumptive Y-cells (Class 1; Guillery, 1966) and observed that it was common for those cells to receive from multiple retinal axons (integration) and for the axons to innervate multiple LGN cells (multiplexing). It is well accepted that LGN Y-cells outside the A-layers receive converging Y-cell input and the receptive fields are much larger than any one of their retinal inputs (Kratz et al, 1978;Dreher and Sefton, 1979;Yeh et al, 2009). …”
Section: Amplification/integration Of Retinal Signalsmentioning
confidence: 99%